2010
DOI: 10.1073/pnas.1005974108
|View full text |Cite
|
Sign up to set email alerts
|

Illusory motion perception in blindsight

Abstract: Motion detection is typically spared in blindsight, which results from damage to the striate cortex (area V1) of the brain that is sufficient to eliminate conscious visual awareness and severely reduce sensitivity to luminance contrast, especially for high spatial and low temporal frequencies. Here we show that the discrimination of motion direction within cortically blind fields is not attributable to feature tracking (the detection of changes in position or shape), but is due instead to the detection of firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Given our results indicating the high-speed preference of motion perception based exclusively on spatiotemporal changes in luminance, it is conceivable that the collicular route to MT is the primary pathway for objectless motion perception. Supporting this possibility is evidence that hemianopes with unilateral damage to V1 can discriminate the direction of high-speed motion in their cortically blind hemifield, despite the absence of object/shape discrimination (Azzopardi & Cowey 2001;Barbur et al 1993), and further, that this direction discrimination is based on spatiotemporal changes in luminance rather than changes in shape (Azzopardi & Hock 2011).…”
Section: Neural Pathwaysmentioning
confidence: 98%
See 2 more Smart Citations
“…Given our results indicating the high-speed preference of motion perception based exclusively on spatiotemporal changes in luminance, it is conceivable that the collicular route to MT is the primary pathway for objectless motion perception. Supporting this possibility is evidence that hemianopes with unilateral damage to V1 can discriminate the direction of high-speed motion in their cortically blind hemifield, despite the absence of object/shape discrimination (Azzopardi & Cowey 2001;Barbur et al 1993), and further, that this direction discrimination is based on spatiotemporal changes in luminance rather than changes in shape (Azzopardi & Hock 2011).…”
Section: Neural Pathwaysmentioning
confidence: 98%
“…Additional experiments have indicated that direction discrimination in a hemianope's cortically blind hemifield is based on the detection of spatiotemporal changes in luminance, irrespective of any other stimulus feature (Azzopardi & Hock 2011). These experiments were based on the line motion illusion (previously called polarized gamma motion), which occurs when a surface is present and another surface is presented adjacent to it, or both surfaces are present and one is then removed (Faubert & von Grünau 1995;Hikosaka et al 1993a, b;Kanizsa 1978).…”
Section: Blindsightmentioning
confidence: 99%
See 1 more Smart Citation
“…If the elements of the random dot kinematogram initially change in contrast whilst remaining stationary before the onset of motion then blindsight patients cannot even determine when motion starts, let alone discriminate its speed or direction. Recently Azzopardi and Hock (2011) showed that the responses of blindsight patients to motion are influenced by changes in the contrast polarity of stimuli. If we see a black bar against a grey background extend upwards we see motion in an upward direction whether the extension to the bar is black or white.…”
Section: Motionmentioning
confidence: 99%
“…98). In addition, there is evidence that wavelength information, shape information, and other features of the stimulus do not feature as contents of the subjects' awareness (Azzopardi & Hock, 2011;Weiskrantz et al, 1995).…”
Section: The Argument From Subjective Reportmentioning
confidence: 99%